Dynamic changes in sleep architecture in a mouse model of acute kidney injury transitioning to chronic kidney disease - Hayashi, Naoko; Okabe, Yuto; Tanaka, Kaeko; Kitajima, Mina; Taniguchi, Keisuke; Yanagita, Motoko; Hayashi, Yu (Frontiers in Neuroscience, 2025)
IntroductionSleep disorders are common in individuals with kidney failure. Whether kidney impairment is the direct cause of sleep abnormalities is unclear, however, partly due to confounding factors including comorbidities, dialysis, and drugs.MethodsHere, we used a mouse model of acute kidney injury (AKI) transitioning to chronic kidney disease (CKD) induced by aristolochic acid to examine the effects of kidney impairment on sleep architecture. Each group, comprising 8 10 male mice, underwent cortical electroencephalogram (EEG) and electroencephalogram (EMG) recordings to measure sleep and cortical oscillations.ResultsDuring the acute phase, which models AKI, mice exhibited an approximately 20% increase in non-rapid eye movement sleep (NREMS) amount but reduced NREMS delta power in the EEG, which might be a consequence of systemic inflammation. Notably, in the chronic phase, which models CDK, the NREMS abnormalities were resolved, but rapid eye movement sleep (REMS) amount was largely reduced by approximately 20%. In addition, EEG theta power during both wakefulness and REMS was decreased. EEG slowing during wake and REMS was observed during both AKI and CKD. REMS disturbances in CKD mice correlated with serum levels of creatinine, urea nitrogen, and calcium.DiscussionTogether, these findings provide direct evidence that kidney impairment has dynamic effects on sleep architecture and EEG power spectra, and provide insight into the mechanisms underlying sleep abnormalities in individuals with AKI or CKD. Regarding sleep management in individuals with kidney failure, it is thus crucial to be aware of the possibility that kidney impairment directly causes sleep disturbances independent of treatment, comorbidities, or patient background.